Digital bank transformation: A content analysis of SEABank - Erni Febrina Harahap; I Gede Arya Pering Arimbawa; Ni Luh Ketut Ayu Sudha Sucandrawati; Tanti Widia Nurdiani; Samuel PD Anantadjaya (Jurnal Komunikasi Profesional, 2023)
SEABank is the new digital bank that gives offer with benefit to the customers and predicting their customers capacity well. Though conventional bank also have digital system, SEABank and conventional bank have few differences in features and financial cost. Through Krippendorf content analysis, the topic will be explored moderately and easy to read. The fact that the knowledge and capabilities gap between youngsters and elders make this topic functional for different perspective for SEABank and other digital bank users. The content analysis shows us that even in the middle of dynamic in digital bank and conventional bank, financial literacy will be affected.